2015
DOI: 10.1177/1933719114557898
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Mediated Soluble Fms-Like Tyrosine Kinase 1 Increase Is Not Attenuated in Interleukin 6-Deficient Mice

Abstract: The soluble fms-like tyrosine kinase 1 (sFlt-1), known to be increased in the serum of preeclamptic patients, is a relevant factor in causing maternal symptoms like hypertension and proteinuria. In this study, we aimed to reveal whether hypoxia is a cause of increased sFlt-1 levels and inflammation markers in vivo and whether these symptoms can be attenuated by interleukin 6 (IL-6) depletion. For this purpose, pregnant wild-type (wt) mice or IL-6 À/À mice on embryonic day 16 were placed under either normoxic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…qPCR analysis was performed as described before [22,23]. Briefly, total RNA was isolated from the placenta or egWAT samples with a TriReagent ® solution (Sigma, Steinheim, Germany) and 1 µg was converted into cDNA.…”
Section: Qpcr Analysismentioning
confidence: 99%
“…qPCR analysis was performed as described before [22,23]. Briefly, total RNA was isolated from the placenta or egWAT samples with a TriReagent ® solution (Sigma, Steinheim, Germany) and 1 µg was converted into cDNA.…”
Section: Qpcr Analysismentioning
confidence: 99%
“…[135][136][137][138] The soluble fms-like tyrosine kinase-1 (sFlt-1) acts as a soluble receptor and antagonist against VEGF and PlGF. 150,151 Chronic hypoxia, both in early and late gestation, placental oxidative stress and preeclampsia are all associated with an increased ratio of sFlt-1 to PlGF and VEGF in both the trophoblast and the maternal circulation, and administration of sFlt-1 itself has been found to further increase tissue ROS 137,[152][153][154][155][156][157] ( Figs. 1 and 2).…”
Section: Nitric Oxidementioning
confidence: 99%
“…Since IL-6 seems to be able to pass the placenta, it might be able to affect fetal brain development [249,250]. It is noteworthy that not all studies found evidence of IL-6 placental-fetal transport [251]. IL-6 is able to trigger fetal inflammatory processes both directly via placental transfer and indirectly via placental inflammation [252].…”
Section: Activation Of the Fetal Immune System Influences Animal Offsmentioning
confidence: 99%